Interleukin-4 induces a CD44 high /CD49b high PC3 subpopulation with tumor-initiating characteristics - Erb, Holger H H; Guggenberger, Fabian; Santer, Frédéric R; Culig, Zoran (Journal of cellular biochemistry, 2018)
Pro- and anti-inflammatory cytokines may influence proliferation, migration, invasion, and other cellular events of prostate cancer (PCa) cells. The hyaluronan receptor CD44, which is regulated by Interleukin (IL)-4, is a prostate basal cell marker. CD44high /CD49bhigh expressing cells have been demonstrated to have tumor-initiating characteristics. Here, we aimed to analyze the effects of long-term IL-4 treatment on CD44/CD49b expression, migration, proliferation, and clonogenic potential of basal-like PCa cells. To this end PC3 cells were treated over 30 passages with 5 ng/mL IL-4 (PC3-IL4) resulting in an increased population of CD44high expressing cells. This was concurrent with a clonal outgrowth of cuboid-shaped cells, with increased size and light absorbance properties. Flow cytometry revealed that the PC3-IL4 CD44high expressing subpopulation corresponds to the CD49bhigh population. Isolation of the PC3-IL4 CD44high /CD49bhigh subpopulation via fluorescence-associated cell sorting showed increased migrative, proliferative, and clonogenic potential compared to the CD44low /CD49blow subpopulation. In conclusion, IL-4 increases a PC3 subpopulation with tumor-initiating characteristics. Thus, IL-4, similar to other cytokines may be a regulator of tumor-initiation and hence, may present a suitable therapy target in combination with current treatment options.
Keywords: interleukin-4; nádorová transformace buněk; Humans; PC-3 Cells; nádory prostaty; Prostatic Neoplasms; Integrin alpha2; integrin alfa2; Cell Transformation, Neoplastic; Interleukin-4; Male; buňky PC-3; Hyaluronan Receptors; mužské pohlaví; Neoplasm Proteins; lidé; nádorové proteiny; antigeny CD44